Between Ideality and Reality in The Islamic Literature and Al-Quran: Reception Analysis - Eva Farhah (IAIN Salatiga, 2022)
This research aimed to reveal the roles of Islamic and Arabic literature's history in studying Islamic literature and sciences; Therefore, the reception theory and critical method were used to answer such issues. The reception theory is a discipline that optimizes the roles of readers and interpreters (mufassirīn) in revealing the meaning of Islamic literature and Al-Quran texts. As for the critical method, it is how the readers and interpreters respond, perceive, and interpret the texts of Islamic literary works and Al-Quran, equipped with al-qawā'id wal-ma'ārif, and storage or repertoire (knowledge within the mind of interpreter); Accordingly, the general audiences can comprehensively and contextually understand the text concretization presented by the interpreters. The results showed that analyzing and interpreting Islamic literary text require knowledge related to Arabic literature's history, especially from the early days of Islam to contemporary times. Meanwhile, analyzing and interpreting al-Quran and Hadith texts also require knowledge of Islamic civilization history and other Islamic sciences such as Arabic knowledge (nahwu, sharaf, and balāghah), asbābun-nuzūl (concerning Al-Quran texts), asbābul-wurūd (concerning Hadith texts), and others.